Enactments in Emotionally Focused Couple Therapy: Shaping Moments of Contact and Change. (26th April 2012) - Tilley, Douglas; Palmer, Gail
<x xml:space="preserve">Abstract</x> Emotionally focused couple therapy (EFT) uses enactments to shape responsive attachment‐significant contact and to change couple interaction. In this article, we show how EFT enactments differ from enactments in other therapy approaches, present a theory of EFT enactments, a model for creating EFT enactments, and an extended case example of an EFT enactment.